2015
DOI: 10.1101/gad.250282.114
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Nerfin-1 prevents reversion of neurons into neural stem cells

Abstract: Cellular dedifferentiation is the regression of a cell from a specialized state to a more multipotent state and is implicated in cancer. However, the transcriptional network that prevents differentiated cells from reacquiring stem cell fate is so far unclear. Neuroblasts (NBs), the Drosophila neural stem cells, are a model for the regulation of stem cell self-renewal and differentiation. Here we show that the Drosophila zinc finger transcription factor Nervous fingers 1 (Nerfin-1) locks neurons into differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…On the other hand, absence of Lola leads to neuron-to-NB reversion and tumorigenesis (Southall et al, 2014), but it is crucial for neuronal maintenance only in the optic lobe. Recently, a paper reported that Nerfin-1 loss induces neuron dedifferentiation in both central brain and VNC (Froldi et al, 2015). In the present study, we demonstrate a conserved function for Nerfin-1 in medulla neurons in the optic lobe.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, absence of Lola leads to neuron-to-NB reversion and tumorigenesis (Southall et al, 2014), but it is crucial for neuronal maintenance only in the optic lobe. Recently, a paper reported that Nerfin-1 loss induces neuron dedifferentiation in both central brain and VNC (Froldi et al, 2015). In the present study, we demonstrate a conserved function for Nerfin-1 in medulla neurons in the optic lobe.…”
Section: Discussionsupporting
confidence: 56%
“…A recent study suggests that Nerfin-1 maintains neuron differentiation in both central brains and VNCs (Froldi et al, 2015). In that study, Myc and Target of rapamycin (Tor) were reported to be necessary for the dedifferentiation caused by Nerfin-1 loss.…”
Section: Medulla Neuron Dedifferentiation Caused By Nerfin-1 Loss Is mentioning
confidence: 99%
“…Histidine deprivation inhibits the growth of nerfin-1 but not pros clones or wildtype stem cells Mutations in the zinc finger transcription factor Nerfin-1, which is predominantly expressed in postmitotic neural lineages, provide a useful model for neural dedifferentiation-derived clones in the CNS (Froldi et al, 2015;Xu et al, 2017). In nerfin-1 mutant clones, neurons switch off the expression of differentiation genes in favour of stem cell markers, resulting in tumour-like lineages which exhibit unlimited proliferative potential, that fail to differentiate and are metastatic when transplanted into naive adult hosts (Froldi et al, 2015 and Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In pros clones, however, the NB diameter and nucleolar/nuclear ratio were not significantly affected by histidine dietary withdrawal (Fig 3H, K and L). Furthermore, unlike nerfin-1 NBs which exhibit~3-fold increase in nucleolus/nuclear volume ratio compared to control (Froldi et al, 2015), pros NBs are not significantly different from control NBs in terms of cellular growth ( Fig 4D). This is primarily because pros NB-like cells tend to be much smaller than their wildtype counterparts (Fig 4A-C).…”
Section: Histidine Deprivation Inhibits Ribosome Biogenesis and Nerfimentioning
confidence: 89%
See 1 more Smart Citation